Comparison of three methods for assessment of drug elution: In vitro elution of gentamicin from a collagen-based scaffold - Billings, Caroline; Anderson, David E. (Frontiers in Drug Delivery, 2022)
In vitro drug elution experiments are commonly performed when evaluating fitness of drug delivery devices for in vivo use. Evaluation of drug elution characteristics spans many drug delivery applications including local delivery of antimicrobials and chemotherapeutics; and is of particular interest for prevention and treatment of orthopedic infections. Despite widespread utility, there is little agreement in methodology to perform such studies, and there are recognized limitations in published works. We evaluated three of the most commonly reported in vitro drug elution methods. We utilized a commercially available collagen matrix (Fibro-Gide®, Geistlich) and an antibiotic that is widely used for local antimicrobial therapy (gentamicin). The protocols used were: 1. complete replacement of media and washing of device, 2. complete replacement of media without washing or 3. partial replacement of media. Results show statistically significant differences in elution characteristics among the three methods utilizing this delivery vehicle and drug. These results may provide the framework for moving towards more consistent methodology for in vitro elution experiments and address certain acknowledged limitations in the literature.